Are high school students motivated to attend counseling ? - Hariko, Rezki (COUNS-EDU: The International Journal of Counseling and Education, 2018)
Counseling is the core of the implementation of guidance and counseling services at the school as a whole. The success of counseling is a guarantee for the success of different types of guidance and counseling services. Unfortunately, not many students who voluntarily went to a counselor for help through the implementation of counseling. This research aims to describe the motivation of students to attend counseling. The research used survey method with 316 students of High School students. The results show that most students have not been motivated to follow counseling. Based on these findings, further research is needed on the factors that influence student motivation, as well as the efforts should be done by counselors and other stakeholders to increase students' motivation to attend counseling.